Exploring medical language : - Brooks, Myrna LaFleur (C.V. Mosby, 1998)
Contents: The Instructor's Munual to accompany Exploring Medical Language will assist you in effectively and efficiently planning teaching your medical terminology course. the instructor's manual will provide a suggested course outline, chapter objectives, classroom activities, additional terms not included in the text, transparency masters, and a wealth of multiple choice questions that you can use for quizzes and exams